2023
DOI: 10.1002/jmv.28746
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes loading Tapasin enhance T cell immune response by autophagy to inhibit HBV replication

Abstract: Hepatitis B virus (HBV) specific T cell immune response plays a vital role in viral clearance. Dendritic cell derived exosomes (Dexs) can activate T cell immunity effectively. Tapasin (TPN) is involved in antigen processing and specific immune recognition. In the present study, we elucidated that Dexs loading TPN (TPN-Dexs) could enhance CD8 + T cell immune response and inhibit virus replication in HBV transgenic mice. T cell immune response and the ability of inhibiting HBV replication were measured in HBV tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Numerous reports have shown that autophagy plays an important role in HBV infection and host antiviral immune regulation 10–12,30–32 . In our previous study, we found that ATG5 knockdown inhibited HCV replication through activating the type‐I IFN signaling pathway, leading to enhanced expression of some antiviral ISGs.…”
Section: Discussionmentioning
confidence: 84%
“…Numerous reports have shown that autophagy plays an important role in HBV infection and host antiviral immune regulation 10–12,30–32 . In our previous study, we found that ATG5 knockdown inhibited HCV replication through activating the type‐I IFN signaling pathway, leading to enhanced expression of some antiviral ISGs.…”
Section: Discussionmentioning
confidence: 84%